1999
DOI: 10.1074/jbc.274.14.9258
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C μ Is Negatively Regulated by 14-3-3 Signal Transduction Proteins

Abstract: Recent studies have documented direct interaction between 14-3-3 proteins and key molecules in signal transduction pathways like Ras, Cbl, and protein kinases. In T cells, the 14-3-3 isoform has been shown to associate with protein kinase C and to negatively regulate interleukin-2 secretion. Here we present data that 14-3-3 interacts with protein kinase C (PKC), a subtype that differs from other PKC members in structure and activation mechanisms. Specific interaction of PKC and 14-3-3 can be shown in the T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 44 publications
5
99
0
Order By: Relevance
“…As a feasible explanation to the lack of endogenous PKD activity in the axon, we can assume that inactivation of PKD, e.g., via sequestration by 14-3-3 adapter proteins (Hausser et al, 1999;Taya et al, 2007) is selectively increased in the axons. At the same time, selective dephosphorylation of PKD, the reporter, or both (Uetani et al, 2006) has to be also taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a feasible explanation to the lack of endogenous PKD activity in the axon, we can assume that inactivation of PKD, e.g., via sequestration by 14-3-3 adapter proteins (Hausser et al, 1999;Taya et al, 2007) is selectively increased in the axons. At the same time, selective dephosphorylation of PKD, the reporter, or both (Uetani et al, 2006) has to be also taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescently tagged human wtPKD1-GFP, kdPKD1-GFP (PKC K612W -EGFP), PKD1⌬PH-GFP, or caPKD1-GFP (PKD1 S738/742E ) plasmids have been described previously (Hausser et al, 1999(Hausser et al, , 2002(Hausser et al, , 2005. pEGFP-C1, pEGFP-N1, and pmCherry-N1 vectors were from Clontech Europe (Saint-Germain-enLaye, France) and A. Jeromin, Allen Institute for Brain Science (Seattle, WA), respectively.…”
Section: Expression Constructsmentioning
confidence: 99%
“…It is therefore likely that the downstream effects of PKC⑀ are mediated by the C1 domains. These structures have in several studies been shown to exert different biological effects (Lehel et al, 1995;Pawelczyk et al, 1998;Kiss et al, 1999;Aroca et al, 2000) and to interact with other proteins (Matto-Yelin et al, 1997;Yao et al, 1997;Pawelczyk et al, 1998;Hausser et al, 1999;Johannes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal domain, and the zinc finger motifs in particular, appear to be important in regulating PKD subcellular localization [reviewed in (1)]. There is also a conserved serine autophosphorylation site between the zinc finger motifs that is required for interaction with 14-3-3 protein, whose binding negatively regulates PKD activity (2,3). In addition, the PKD1 regulatory domain possesses an alanine and proline rich apolar region in the N-terminus, whereas the PKD2 regulatory domain has a proline rich region, and also contains a serine-rich linker between the zinc finger motifs.…”
Section: Introductionmentioning
confidence: 99%